Features of the discursive environment as a source for creating meaning in online communication (using the example of social networks) - N. A. Yushkina; M. A. Panarina (Цифровая социология, 2019)
With the spread of online communication, more and more attempts are being made to study it as a process occurring in different discursive spaces. In the article, using the example of a single message hosted on several social networks, the discursive conditions and the possibilities of various social media to influence the content of the meanings, created within their environment, have been analyzed. The subject of the research was the discursive characteristics of representations of a single message in various social networks. The purpose of the paper is presentation of a theoretical and methodological approach for cross-platform analysis of social media discourse, which, if desired, can be expanded on a larger data file, taking into account the results of the qualitative critical discourse analysis of the case introduced. The method of critical discourse analysis (CDA) has been used, which allows you to identify and analyze social structures in the framework of dialectical relationships. In the course of the study and analysis, it was revealed, that even in the case, when using the variable capabilities of various social networks to create and transmit meanings is not a deliberate strategy of a single institution, its messages were filled with different semantic content, which means, that they have different convincing and legitimizing opportunities. This was due to the inability to avoid certain conditions of production, creation and distribution of content, set by the policy of social networks. Social network, as a communicative space, creates a mode of production, distribution and consumption of content, and in this mode, communication is already carried out. Due to the specific features of each network, one can say, that they create different discursive spaces.